2021
DOI: 10.1371/journal.pone.0253087
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of parental distress during and after the first COVID-19 lockdown phase: A two-wave longitudinal study

Abstract: Background In these unpredictable times of the global coronavirus disease 2019 (COVID-19) pandemic, parents worldwide are affected by the stress and strain caused by the physical distancing protocols that have been put in place. Objective In a two‐wave longitudinal survey, we investigated the levels of parental stress and symptoms of anxiety and depression in a sample of parents at two time points; during the implementation of the strictest physical distancing protocols following the onset of the COVID-19 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 61 publications
7
31
0
1
Order By: Relevance
“…Such strategies have previously been found to be fruitful in alleviating symptoms of anxiety and depression in non-pandemic settings (e.g., Morgan et al, 2017 ). Other vulnerable subgroups than those identified in the present study have also been noted in the literature, such as adolescents and parents (e.g., Commodari & La Rosa, 2020 ; Johnson et al, 2021 ), collectively highlighting the necessity to direct increased efforts toward groups that are more skewedly affected by the pandemic.…”
Section: Discussionsupporting
confidence: 77%
“…Such strategies have previously been found to be fruitful in alleviating symptoms of anxiety and depression in non-pandemic settings (e.g., Morgan et al, 2017 ). Other vulnerable subgroups than those identified in the present study have also been noted in the literature, such as adolescents and parents (e.g., Commodari & La Rosa, 2020 ; Johnson et al, 2021 ), collectively highlighting the necessity to direct increased efforts toward groups that are more skewedly affected by the pandemic.…”
Section: Discussionsupporting
confidence: 77%
“…One-year post quarantine, depression levels were significantly associated with both marital and employment status of the study participants while stress levels were significantly associated with participants' educational levels as illustrated in the results section. These two factors were radically affected due to COVID-19 pandemic, and apparently there is an association between one's marital status, employment status and their psychological health as implied in the present study and other studies with agreed findings [18,19]. On the contrary, a conducted study in Nepal reported different results as they found anxiety and depression were independent of the participants sociodemographic factors [20].…”
Section: Discussionsupporting
confidence: 60%
“…None of the included individuals had severe stress during quarantine or one year later, however, a significant reduction of 8% was observed in the prevalence of moderately stressed persons between the two measurements. another study employing parents to assess their psychological well-being during and after strict protocols related to the pandemic, and the perceived results showed significant decrease in depression and anxiety symptoms [18].…”
Section: Discussionmentioning
confidence: 96%
“…Such strategies have previously been found to be fruitful in alleviating symptoms of anxiety and depression in non-pandemic settings (e.g., Morgan et al, 2017). Other vulnerable subgroups than those identified in the present study have also been noted in the literature, such as adolescents and parents (e.g., Commodari & La Rosa, 2020;Johnson et al, 2020;Johnson et al, 2021), collectively highlighting the necessity to direct increased efforts toward groups that are more skewedly affected by the pandemic.…”
Section: Prevalence Of Anxiety and Depressive Symptomssupporting
confidence: 63%